1986
DOI: 10.1007/bf00354061
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar posterior marginal intra-osseous cartilaginous node

Abstract: This report concerns 12 patients, eight young adults and four adolescents, presenting with lumbar or sciatic pain. This was associated with an unusual defect of the inferior and posterior edges of the vertebral bodies of L4 or L5, together with a small bony ridge protruding into the spinal canal. We found 11 similar cases in the literature, all involving adolescents except for one young adult. It has been considered to be the result of a fracture of the posterior ring apophysis in association with a herniated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
5

Year Published

1988
1988
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 8 publications
2
37
0
5
Order By: Relevance
“…Second, all patients suffered myelopathy or radiculopathy that warranted surgery, whereas neurological complications of SD; especially, in adults with mild kyphosis, were considered rare in the past [5,19]. Adequate evidence has shown that SD and its radiographic changes promote disc degeneration [6][7][8][9]20]. This was also demonstrated in our study in which SN, IE, PBA and WV were all found to enhance disc herniation in the TLDH group (Table 5).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Second, all patients suffered myelopathy or radiculopathy that warranted surgery, whereas neurological complications of SD; especially, in adults with mild kyphosis, were considered rare in the past [5,19]. Adequate evidence has shown that SD and its radiographic changes promote disc degeneration [6][7][8][9]20]. This was also demonstrated in our study in which SN, IE, PBA and WV were all found to enhance disc herniation in the TLDH group (Table 5).…”
Section: Discussionsupporting
confidence: 71%
“…It was frequently found to appear together with other signs of SD [8]. Previous studies reported PBA would occur at the lower lumbar spine at a low incidence and tend to promote symptomatic disc herniation [8,26,27]. The high incidence of PBA in symptomatic TLDH patients may be partly attributed to increased thoracolumbar kyphosis, as observed in this series, which could produce increased stretching stress on the posterior annulus of the discs.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations